Childhood CT scans and cancer risk: impact of predisposing factors for cancer on the risk estimates. (15th February 2016) - Journy, N; Roué, T; Cardis, E; Le Pointe, H Ducou; Brisse, H; Chateil, J-F; Laurier, D; Bernier, M-O
Abstract: To investigate the role of cancer predisposing factors (PFs) on the associations between paediatric computed tomography (CT) scan exposures and subsequent risk of central nervous system (CNS) tumours and leukaemia. A cohort of children who underwent a CT scan in 2000–2010 in 23 French radiology departments was linked with the national childhood cancers registry and national vital status registry; information on PFs was retrieved through hospital discharge databases. In children without PF, hazard ratios of 1.07 (95% CI 0.99–1.10) for CNS tumours (15 cases) and 1.16 (95% CI 0.77–1.27) for leukaemia (12 cases) were estimated for each 10 mGy increment in CT x-rays organ doses. These estimates were similar to those obtained in the whole cohort. In children with PFs, no positive dose-risk association was observed, possibly related to earlier non-cancer mortality in this group. Our results suggest a modifying effect of PFs on CT-related cancer risks, but need to be confirmed by longer follow-up and other studies.